2010
DOI: 10.4049/jimmunol.0902314
|View full text |Cite
|
Sign up to set email alerts
|

Major Differences in the Responses of Primary Human Leukocyte Subsets to IFN-β

Abstract: Treatment of cell lines with type I IFNs activates the formation of ISGF3 (STAT1/STAT2/IRF9), which induces the expression of many genes. To study this response in primary cells, we treated fresh human blood with IFN-β and used flow cytometry to analyze phosphorylated STATs1, 3 and 5 in CD4+ and CD8+ T cells, B cells, and monocytes. The activation of STAT1 was remarkably different among these leukocyte subsets. In contrast to monocytes, CD4+ and CD8+ T cells, few B cells activated STAT1 in response to IFN-β, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 58 publications
10
56
0
Order By: Relevance
“…Similarly, our previous study of healthy subjects showed significantly fewer CD4 + T cells than monocytes with activated STAT3 in response to 500 IU/mL IFN-β1a in vitro (9). However, we also observed previously, in healthy subjects, by using the same in vitro conditions, that significantly fewer CD4 + T cells and B cells activated STAT1 in comparison with monocytes (9).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Similarly, our previous study of healthy subjects showed significantly fewer CD4 + T cells than monocytes with activated STAT3 in response to 500 IU/mL IFN-β1a in vitro (9). However, we also observed previously, in healthy subjects, by using the same in vitro conditions, that significantly fewer CD4 + T cells and B cells activated STAT1 in comparison with monocytes (9).…”
Section: Resultssupporting
confidence: 86%
“…We previously found significant differences in the activation of STATs 1, 3, and 5 among leukocyte subsets after stimulation of whole blood of healthy donors in vitro with IFNβ1a, and linked these differences to differential induction of apoptosis (9). In a control experiment (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations